Pengaruh Stres Kerja, Lingkungan Kerja Fisik, dan Motivasi Kerja terhadap Kepuasan Kerja Pegawai Dinas Tenaga Kerja Kabupaten Sleman - Puti Wijiasih; Tri Harsini Wahyuningsih; Dian Astrini Amir (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2020)
This research aims to analyze the influencejobstress, physical work environment and jobmotivationto the employee’sjobsatisfactionDinas Tenaga KerjaKabupatenSleman. This research was conducted on December 2019 Dinas Tenaga KerjaKabupatenSleman. The data collection was carried out using a questionnaire. The population in this study were all employees of the Dinas Tenaga KerjaKabupatenSleman. The sample in this study were 35 employees of the Sleman Regency Manpower Office, and the sample was taken by census. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially, job stress has a negative and significant effect on employee job satisfaction, physical work environment has a positive and significant effect on employee job satisfaction, and motivation has a positive and significant effect on employee job satisfaction.